Analisis pajak pembangunan I perhotelan sebagai sumber pendapatan asli daerah: Studi kasus kotamadya Yogyakarta - Ahmad Jamli; Astuti Rahayu (Universitas Islam Indonesia, 1997)
In organising the deregulation principle of the organization of regional government the national government gives an authority for the regional government to organize its own region. Therefore, the regional government has to raise regional tax to fund its region expenditures.